2001
DOI: 10.1097/00000542-200107000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Shannon Entropy Applied to the Measurement of the Electroencephalographic Effects of Desflurane

Abstract: The Shannon entropy seems to be a useful electroencephalographic measure of anesthetic drug effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(50 citation statements)
references
References 1 publication
0
49
0
1
Order By: Relevance
“…The filtered EEG signal (0.0 -30 Hz) was sampled at a rate of 1,000 Hz, using commercially available EEG equipment (Grass Instruments). Home-made software based on the Shannon spectral entropy method (22) was used to quantify EEG data and to calculate the spectral entropy index (SEI Յ 1), where a high SEI value indicates a high brain activity level. The EEG signal was divided into epochs of 10-s duration, and then the spectral entropy index was calculated for each epoch in the 0.3-to 30-Hz frequency range.…”
Section: [2]mentioning
confidence: 99%
See 1 more Smart Citation
“…The filtered EEG signal (0.0 -30 Hz) was sampled at a rate of 1,000 Hz, using commercially available EEG equipment (Grass Instruments). Home-made software based on the Shannon spectral entropy method (22) was used to quantify EEG data and to calculate the spectral entropy index (SEI Յ 1), where a high SEI value indicates a high brain activity level. The EEG signal was divided into epochs of 10-s duration, and then the spectral entropy index was calculated for each epoch in the 0.3-to 30-Hz frequency range.…”
Section: [2]mentioning
confidence: 99%
“…The in vivo 31 P MT approach (9-12) was applied to measure both the forward chemical exchange fluxes (F f ) from PCr to ATP [i.e., forward CK reaction flux (F f , CK ) related to the PCr 3 ATP reaction catalyzed by CK] and from P i to ATP [i.e., forward ATPase reaction flux (F f,ATPase ) related to the Pi 3 ATP reaction catalyzed by ATPase] by selectively saturating the ␥-ATP resonance peak under varied brain activity states in the rat. The rat brain activities were determined by EEG measurements and quantified by the spectral entropy index (SEI) based on the Shannon spectral entropy method (22). The details regarding the measurements of F f , ATPase , F f , CK , and SEI may be found in Materials and Methods.…”
mentioning
confidence: 99%
“…(1)(2)(3) . Studies demonstrated the usefulness of shannon entropy and the approximate entropy to describe the EEG changes during desflurane anaesthesia (4) . The Datex omeda S/5 entropy module is the first commercially available monitor based on the spectral entropy (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…The larger the entropy, the greater the uncertainty and randomness. In the present study, the entropy used to process EEG can be viewed as a measure of the order in the signal, which measures the skewness and uncertainty [76]. In the case of random variables with known probability distribution, the entropy is defined by…”
Section: Feature Extractionmentioning
confidence: 99%